Strength Model for Concrete in Near-Reinforcement Region - Vladimir I. Kolchunov; Natalia V. Fedorova; Tatiana A. Iliushchenko (Structural Mechanics of Engineering Constructions and Buildings)
The relevant problem of concrete strength in the near-reinforcement zone is solved as a problem of volumetric stress-strain state with the “closure” of output integral parameters of this zone on the framework of the whole reinforced concrete element, synthesizing hypotheses and dependencies of various disciplines of solid mechanics, including fracture mechanics. The model of reinforced concrete element takes into account Vl.I. Kolchunov’s effect of reinforced concrete, which describes the mechanism of formation and development of transverse and longitudinal cracks. In this respect, generalized hypotheses of linear and shear strains for warping and gradients of relative mutual displacements of reinforcement and concrete are adopted. New functionals of reinforced concrete are constructed, which are consistent with the physical interpretations of the strength of cross-sections of bar elements in near-reinforcement zones. Constitutive equations for the concrete matrix, which models zones between transverse cracks, are written. The displacement components for the nearreinforcement zone in relation to the crack opening width at the “concrete-reinforcement” contact interface in transverse, longitudinal and radial cracks, respectively, are found. The use of the adopted assumptions and a multi-level calculation approach for the near-reinforcement region brings the model significantly closer to a real evaluation of the physical phenomena.